The Relationship of Serum Magnesium Levels with Etiology, Lesion Size, and Localization in Ischemic Stroke - Mustafa Ülker; Tuğçe Toptan; Rahşan Karacı; Mehmet Demir; Saime Füsun Domaç (Boğaziçi Tıp Dergisi, 2022)
INTRODUCTION: Magnesium is known to have important effects on vascular system and deficiency of magnesium triggers vasoconstriction and facilitates vascular endothelial damage. There were conflicting results in several studies searched for relationship between magnesium levels, etiologic subtypes, and lesion size in ischemic stroke. We aimed to examine relationship between serum magnesium levels and etiology of stroke as well as lesion size and localization. METHODS: A total of 545 patients over the age of 18 years who presented within the first 24 h of acute ischemic stroke and 189 healthy controls were included in the study. Patients were grouped according to TOAST classification and also as anterior and posterior circulation infarcts. Infarct volume was estimated using MRI scan as large (≥5 cm3) and small (<5 cm3) infarct. The relationship between serum magnesium levels and etiology, lesion size, and localization was examined. RESULTS: Serum magnesium level was 1.90+-0.23 mg/dL in the patient group and 1.93+-0.18 mg/dL in the control group, and no statistically significant difference was found (p=0.11). The mean magnesium level was 1.90+-0.2 mg/dL in the atherothrombotic; 1.87+-0.2 mg/dL in the cardioembolic; 1.88+-0.18 mg/dL in the lacunar; 1.92+-0.2 mg/dL in the undetermined; and 1.91+-0.2 mg/dL in the other stroke group. There was no statistically significant difference between the magnesium levels according to etiology (p=0.25) and localization (p=0.109).The mean magnesium level was 1.87+-0.24 mg/dL and 1.91+-0.2 mg/dL in the large and small infarct groups, respectively. An inverse rela-tionship between mean magnesium levels and the infarct size was found (p=0.044, r=−0.087). DISCUSSION AND CONCLUSION: Our results suggest that Mg may play a role in the pathophysiology of infarction and relatively high Mg levels may limit the lesion size.